Risk of Melanoma With Phosphodiesterase Type 5 Inhibitor Use Among Patients With Erectile Dysfunction, Pulmonary Hypertension, and Lower Urinary Tract Symptoms. Issue 7 (5th June 2018) - Shkolyar, Eugene; Li, Shufeng; Tang, Jean; Eisenberg, Michael L.
Abstract: Background: Phosphodiesterase type 5 inhibitors (PDE5is), a treatment for erectile dysfunction, pulmonary hypertension (pHTN), and lower urinary tract symptoms (LUTS), have been implicated in melanoma development. Aim: We sought to determine the association between PDE5i use and melanoma development among patients with erectile dysfunction, pHTN, and LUTS. Methods: This was a retrospective cohort study of subjects contained within the Truven Health MarketScan claims database, which provides information on insurance claims in the United States for privately insured individuals, from 2007–2015. Individuals taking PDE5i were identified through pharmacy claims. A comparison group of men diagnosed with conditions for which PDE5i are prescribed was assembled. Outcomes: Cox proportional hazard models were used to estimate the hazard ratio (HR) (95% CI) of incident melanoma, basal cell carcinoma, and squamous cell carcinoma. Results: Of 610, 881 subjects prescribed PDE5i, 636 developed melanoma (0.10%). The control group had 8, 711 diagnoses of melanoma. There was an association between increased PDE5i tablet use and melanoma (HR 1.05, 95% CI 1.05–1.09). This association was also present between PDE5i use and basal cell carcinoma (HR 1.04, 95% CI 1.02–1.07) and squamous cell carcinoma (HR 1.04, 95% CI 1.01–1.07). In patients with pHTN and LUTS prescribed PDE5is, there was no relationship between exposure and melanoma incidence (HR 0.74, 95% CI 0.48–1.13; and HR 1.03, 95% CI 0.97–1.10, respectively). Clinical Implications: There is little evidence for a clinically relevant association between PDE5i use and melanoma incidence. Strengths & Limitations: Our current work represents the largest study to date evaluating the relationship between PDE5i use and melanoma risk, and the first to examine all current indications of PDE5i use among men and women. Limitations include a patient population limited to commercially insured individuals, unknown patient medication compliance, and lack of information on patient skin type, lifestyle, and sun-exposure habits. Conclusion: There is a slight association between higher-volume PDE5i use and development of melanoma, basal cell carcinoma, and squamous cell carcinoma. This association among all skin cancers implies that confounding may account for the observed association.